2010
DOI: 10.1123/ijsnem.20.6.475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Omega-3 Polyunsaturated Fatty Acids on the Skeletal-Muscle Blood-Flow Response to Exercise in Rats

Abstract: The polyunsaturated fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) affect vascular relaxation and involve factors (e.g., nitric oxide) that contribute to exercise-induced increases in skeletal-muscle blood flow (Q). The authors investigated whether DHA and EPA supplementation augments skeletal-muscle Q and vascular conductance (VC) and attenuates renal and splanchnic Q and VC in exercising rats. Rats were fed a diet of 5% lipids by weight, of which 20% was DHA and 30% EPA (PUFA group, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Guen et al [65] reported that DHA-enriched supplementation improves endurance exercise capacity and skeletal muscle mitochondrial function in murine skeletal muscle. Stebbins et al [66] reported that DHA + EPA enhances skeletal-muscle blood and vascular conductance in active skeletal muscle (especially type I and IIa fibers) and that the increase in muscle blood is due to an increase in cardiac output secondary to increases in vascular conductance [66]. However, we believe that there are differential effects of PUFAs on the muscle [67].…”
Section: Effects On Skeletal Musclesmentioning
confidence: 74%
“…Guen et al [65] reported that DHA-enriched supplementation improves endurance exercise capacity and skeletal muscle mitochondrial function in murine skeletal muscle. Stebbins et al [66] reported that DHA + EPA enhances skeletal-muscle blood and vascular conductance in active skeletal muscle (especially type I and IIa fibers) and that the increase in muscle blood is due to an increase in cardiac output secondary to increases in vascular conductance [66]. However, we believe that there are differential effects of PUFAs on the muscle [67].…”
Section: Effects On Skeletal Musclesmentioning
confidence: 74%
“…In rats, supplementation with fish-derived fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) enhanced skeletal muscle blood flow during exercise (Stebbins, Hammel, Marshal, Spangenberg, & Musch, 2010). Similarly, in healthy young male humans, dietary fish oil supplementation for 4-weeks resulted in increased resting femoral arterial blood flow (Pearson, Johnson, & Robins, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They speculated that these findings may have implications for patients with cardiovascular disease and exercise intolerance. In a follow-up study, Stebbins et al (2010) showed that supplementation with EPA and DHA can augment the contraction-induced increases in skeletal-muscle blood flow and conductance in exercising rats, therefore resulting in strong correlations between changes in these two variables and the percent sum oxidative fibers (Types I and IIa) observed in the individual muscles or muscle parts. These augmentations in blood flow and conductance occurred in the absence of any changes in perfusion pressure (i.e., mean arterial pressure) or heart rate.…”
Section: Omega-3 Fatty Acids and Exercising Cardiac Functionmentioning
confidence: 99%
“…In addition, positive effects on DOMS may be augmented by the ability of n-3 PUFAs to increase blood flow (Stebbins, Hammel, Marshal, Spangenberg, & Musch, 2010;Walser, Giordano, & Stebbins, 2006), thereby aiding in a more rapid nutrient delivery postexercise. However, further studies are needed to determine whether n-3 PUFAs may, in fact, produce analgesic effects.…”
Section: Omega-3 Fatty Acids Muscle Damage and Inflammatory Responsmentioning
confidence: 99%